The requirements which should be available in the judge of grievance in Islamic Law, Jordanian Law and Saudi Law - Younes, Abed Al Salam Isaa M. Bani; El-Seoudi, Abdel Wadoud Moustafa Moursi; Muhammad Husni, Ahmad (American-Eurasian Network for Scientific Information (AENSI Publisher), 2012)
This study discusses the requirements that should be available in the judge of grievancesin Jordanian Law and Saudi Law comparatively with Islamic jurisprudence. It attempts to clarify whether the requirements which are regulated in these two laws agree or disagree with the requirements which are regulated in Islam. This study is selected because of its importance in our life. It helps the individual who is specialized in the field of judgment to know if he is competent or notcompetent to be a judge of grievances. It also helps the individual to know if the judge who is nominated in grievances has or does not have these requirements. This study depends on qualitative methodology where the viewpoints of jurists are collected and the legitimate bases on which their viewpoints are built. It depends also on analytic methodology by analyzingthe legal articles and the collected viewpoints. Besides that, the study depends on quantitativemethodology by referring to grievances courts. The conclusion of this study is that the requirements of the judge of grievances in Jordanian law are different from those which are regulated in Islamic jurisprudence. This is because Jordanian Law overlooked some requirements in Islamic jurisprudence and, at the same time, added other requirements that are not regulated in it. Meanwhile, the Saudi Law agrees absolutely with the requirements of Islamic jurisprudence.